2005
DOI: 10.2136/vzj2004.0172
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Models of Vadose Zone Flow and Transport beneath the Pajarito Plateau, Los Alamos, New Mexico

Abstract: field observations. To best develop and test conceptual models, supporting data should be derived using a num-The Pajarito Plateau in northern New Mexico, on which the Los ber of observational techniques and include a variety Alamos National Laboratory is situated, is characterized by a thick of data types. vadose zone overlying the regional aquifer of the western Espanola Basin. In this study, conceptual models of vadose zone flow and Los Alamos National Laboratory (the Laboratory or transport processes are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Perched-water zones at much greater depths affect flow and contaminant transport at a large number of arid U.S. Department of Energy (DOE) sites, such as Yucca Mountain (Wu et al 1999(Wu et al , 2004, the Idaho National Engineering and Environmental Laboratory (INEEL; Nimmo et al 2002Nimmo et al , 2004Duke et al 2004;Wang et al 2010), the Pantex Plant in Amarillo, Texas (Adam et al 2004), and the Los Alamos National Laboratory (LANL; Birdsell et al 2004;Robinson et al 2005Robinson et al , 2011.…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Perched-water zones at much greater depths affect flow and contaminant transport at a large number of arid U.S. Department of Energy (DOE) sites, such as Yucca Mountain (Wu et al 1999(Wu et al , 2004, the Idaho National Engineering and Environmental Laboratory (INEEL; Nimmo et al 2002Nimmo et al , 2004Duke et al 2004;Wang et al 2010), the Pantex Plant in Amarillo, Texas (Adam et al 2004), and the Los Alamos National Laboratory (LANL; Birdsell et al 2004;Robinson et al 2005Robinson et al , 2011.…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
“…An extensive set of observations made in deep wells makes this plateau one of the most studied vadose zones among research efforts targeted at understanding mechanisms that give rise to perched water and the hydraulics of perched-water zones (e.g., Birdsell et al 2004;Kwicklis et al 2005;Robinson et al 2011). A large number of perched-water zones at LANL are located below wet canyons, suggesting that in addition to perching horizons, locally high percolation rates with values up to 1 m/yr are required to yield saturated conditions (Kwicklis et al 2005).…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
“…In undulating landscapes, however, where the size of the vadose zone will generally be much larger, higher travel time is expected. In arid environments, for instance, the vadose zone can be hundreds of meters thick, and infiltration fluxes very low [10], resulting in the residence time of water ranging from several hundreds to thousands of years [5]. However, also in such a deep vadose zone, flow can be extremely fast.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, detailed large‐scale, multidimensional models of variably saturated systems with perched water are relatively rare because of the computational challenges involved. Prominent examples of large‐scale, multi‐dimensional variably saturated models include the three‐dimensional (3D), site‐scale model of the unsaturated zone at Yucca Mountain, which was under consideration as a high‐level radioactive waste repository (Liu et al, 2003; Wu et al, 2006), and models of moisture and contaminant movement beneath wet canyons at the Los Alamos site in New Mexico (Birdsell et al, 2005; Robinson et al, 2005). In both instances, modeling demonstrated that significant lateral redistribution of infiltration in the unsaturated zone occurs along low‐permeability perching layers.…”
mentioning
confidence: 99%
“…The analysis of flow and transport pathways near and through perched water at Rainier Mesa can help clarify flow and transport behavior at other existing and potential DOE waste‐storage sites in the arid west where the presence of deep perched water complicates the understanding and monitoring of radionuclide transport. These sites include (i) the Radioactive Waste Management Complex at the Idaho National Laboratory, where lateral flow has been observed in the sedimentary interbeds between lava flows (Duke et al, 2007); (ii) Yucca Mountain, a proposed site for high‐level nuclear waste disposal in volcanic tuffs in southern Nevada, where the stratigraphic and structural setting promotes perching, lateral flow, and possible fault drainage beneath the proposed repository (Bagtzoglou, 2003a, 2003b; Flint et al, 2001, 2002); and (iii) the Los Alamos National Laboratory (LANL) site in northern New Mexico, where perched water above low‐permeability tuff layers beneath wet canyons also creates the potential for lateral flow and complex vadose zone transport paths (Robinson et al, 2005; Birdsell et al, 2005).…”
mentioning
confidence: 99%